(untitled) (TEST Trento Student Law Review, 2020)
The effectiveness, fairness and legitimacy of the Investor-State Dispute Settlement (ISDS) mechanism is the hallmark of a trust-based and justice-oriented legal framework for international investments. The jurisprudential and institutional implications of inconsistent decision-making processes in the ISDS mechanism have led to disagreements and geo-political cleavages among various States in the contemporary context. This is also because of the main concerns in the ISDS framework about sovereignty and regulatory chill, inconsistency of the awards, knowledge asymmetries between the developed and the developing world. The article examines the most relevant scholars’ contributions and the jurisprudence relating to investment disputes in order to point out the weaknesses of the actual ISDS system and to propose possible solutions, with a special attention to substantive reforms. These solutions are proposed on the basis of a knowledge perspective approach aiming to guarantee developing countries fair treatment and real possibilities of further development.